APPLICATION OF TAGUCHI METHOD IN OPTIMIZING INJECTION MOLDING PARAMETERS TO NETTO OF BIORING CONE CUP PRODUCTS - Pramestiani, Ika; Karuniawan, Bayu Wiro; Rachman, Farizi (Universitas Maarif Hasyim Latif, 2023)
Bioring Cone Cup products are produced by Sukodono molding industry with injection molding machine. However, at the beginning of production in getting the parameter value still uses a trial and error system, so this problem results in defects that cause the weight of the product is not in accordance with the agreement so that this product must be recycled again by spending a long time. With this problem, the company suffered losses because it had to pay compensation for production delays. So that research is needed that discusses the optimization of injection molding parameters on the net response of bioring cone cup products. This research uses the parameters of injection pressure, injection temperature, and cooling time. The method used is taguchi with signal to noise ratio criteria, namely smaller is better to determine the effect of factors and also the optimal parameters for the production process. From the experimental results, the optimal combination of variables is obtained, namely the injection pressure parameter at level 1 with a value of 80 bar, injection temperature at level 3 with a value of 230 , and cooling time at level 3 with a value of 0.5 seconds. Produk Bioring Cone Cup diproduksi oleh industri molding Sukodono dengan mesin injection molding. Namun pada awal produksi dalam mendapatkan nilai parameter masih menggunakan sistem trial and error, sehingga permasalahan ini mengakibatkan adanya cacat yang menyebabkan berat produk tidak sesuai kesepakatan sehingga produk ini harus didaur ulang kembali dengan menghabiskan waktu yang cukup lama. Dengan permasalahan tersebut, perusahaan ini mengalami kerugian dikarenakan harus membayar kompensasi keterlambatan produksi. Sehingga dibutuhkan penelitian yang membahas optimalisasi parameter injection molding terhadap respon netto produk bioring cone cup. Penelitian ini menggunakan parameter injection pressure, injection temperature, dan cooling time. Metode yang digunakan adalah taguchi dengan kriteria rasio signal to noise yaitu smaller is better untuk mengetahui pengaruh factor dan juga parameter yang optimal untuk proses produksi. Dari hasil eksperimen, didapatkan hasil kombinasi variabel yang optimal yaitu parameter injection pressure pada level 1 dengan nilai 80 bar, injection temperature pada level 3 dengan nilai 230 , dan cooling time pada level 3 dengan nilai 0,5 detik.